2023
DOI: 10.3390/ijms241914773
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Polycan, a β-Glucan from Aureobasidium pullulans SM-2001, on Inflammatory Response and Intestinal Barrier Function in DSS-Induced Ulcerative Colitis

Hyun Ju Do,
Young-Suk Kim,
Tae Woo Oh

Abstract: Ulcerative colitis (UC), a subtype of inflammatory bowel disease, is a chronic gastrointestinal inflammatory disease with unclear etiology and pathophysiology. Herein, we determined the effects of extracellular polysaccharides purified from Aureobasidium pullulans SM-2001 (Polycan) on tight junction protein expression, inflammation, and apoptosis in a dextran sodium sulfate (DSS)-induced acute colitis model. Fifty mice were divided into normal, DSS, DSS + Polycan 250 mg/kg (Polycan 250), DSS + Polycan 500 mg/k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 39 publications
1
0
0
Order By: Relevance
“…UC-associated disorders could activate cytokines, eliciting a protective immune cell response and inducing the production of TNF-α and NO. It was reported that DSS triggered inflammation by provoking the excessive production of cytokines, consistent with the increases in TNF-α and NO levels in colon tissues of mice by DSS treatment in our current study. On the contrary, PSEO treatment significantly lowered the DSS-induced increases in TNF-α and NO levels in colon tissues of mice.…”
Section: Discussionsupporting
confidence: 91%
“…UC-associated disorders could activate cytokines, eliciting a protective immune cell response and inducing the production of TNF-α and NO. It was reported that DSS triggered inflammation by provoking the excessive production of cytokines, consistent with the increases in TNF-α and NO levels in colon tissues of mice by DSS treatment in our current study. On the contrary, PSEO treatment significantly lowered the DSS-induced increases in TNF-α and NO levels in colon tissues of mice.…”
Section: Discussionsupporting
confidence: 91%